ANALISIS YURIDIS TERHADAP UNSUR-UNSUR NOODWEER DALAM PUTUSAN PENGADILAN NEGERI BANDUNG NOMOR 162/PID.B/2021/PN.BDG - Meidiana Novriyanti; Mia Hadiati (Jurnal Hukum Adigama, 2022)
Polygamy is a form of marriage that is often problematic in society because it invites controversial views, this is because polygamy sometimes does not promise justice and prosperity for the life of the wife and children, especially if polygamy is allowed for reasons not stipulated in Islamic law or Marriage Law. This study discusses how the Bojonegoro Religious Court judges granted a polygamy permit application that was not in accordance with the provisions of the Marriage Law and KHI in the Court Verdict Number 342/PDT.G/2019/PA.BJN. The writer uses normative research using qualitative methods and the material was obtained from the literature study. The results of this study indicate that the granting of polygamy permits is based on alternative and cumulative requirements in Articles 4 and 5 of the Marriage Law. In addition, polygamy permits are also based on fairness to their wives. However, the reasons put forward in case Number: 342/PDT.G/2019/PA.BJN are not regulated in Article 4 Paragraph (2) of the Marriage Law of Jo. Article 57 of the KHI and can cause injustice to his wife and children in the future because there is no emergency situation found in the applicant's condition to be allowed to have polygamy.